Activated carbon-chitosan based adsorbent for the efficient removal of the emerging contaminant diclofenac: Synthesis, characterization and phytotoxicity studies. (November 2022) - Kumar, Ajit; Patra, Chandi; Rajendran, Harish Kumar; Narayanasamy, Selvaraju
Abstract: The rise in pharmaceutical pollutants due to their unregulated discharge in pharmaceutical wastewater has landed them as emerging contaminants that would gradually affect the aquatic ecosystem and human life. The current study emphasizes the adsorptive elimination of one such emerging pharmaceutical pollutant, i.e., Diclofenac (DIF), using a synthesized adsorbent vis. Activated carbon-chitosan beads (ACCB). The morphological and physicochemical properties of the prepared adsorbent, ACCB and its interaction with the DIF species were investigated. Process parameters influencing the adsorptive interactions between ACCB and DIF were optimised. DIF was efficiently adsorbed at optimised initial DIF pH of 6.0 and ACCB dosage of 1.5 mg/mL at an incubation temperature of 40 °C. Freundlich isotherm model showed the best fit (R 2  = 0.98) with the experimental data to conclude that the adsorbent surface is heterogenous, promoting multilayer adsorption. As depicted from the Langmuir isotherm model, the maximum theoretical adsorption capacity was 99.29 mg/g. The seed toxicity assay confirmed the efficacy of ACCB in the adsorptive removal of DIF species from aqueous setups, making the post-treated solution fit enough for seed germination. Graphical abstract: Image 1 Highlights: Activated carbon-chitosan beads (ACCB) have been successfully synthesized. The porous structure and frame network in ACCB were validated using scanning electron microscopy. Recyclability and phytotoxicity analysis shows the efficacy of ACCB. Spent ACCB was quickly and easily separated from the reaction mixture.